EFFICACY OF RITUXIMAB IN STEROID-SENSITIVE NEPHROTIC SYNDROME (Herald of the National Children's Medical Center, 2025)
Steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) have significant clinical importance for the quality of life in children. SSNS is characterized by frequent relapses, while SRNS carries a high risk of chronic progression and renal failure. Various immunosuppressive agents are used in treatment; however, in 10–20% of cases, they do not provide sufficient efficacy. In such cases, monoclonal antibody agents like rituximab (RTX) are required.
Keywords: steroid-sensitive nephrotic syndrome; rituximab; immunosuppressive therapy; remission; children; monoclonal antibody